ONE-STOP INTEGRATED SERVICE SYSTEM TO IMPROVE COMMUNITY SERVICES IN PAYING VEHICLE TAXES AT SAMSAT KABANJAHE - Dewanta Meliala; Syafruddin Ritonga; Indra Muda (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article discusses the implementation of One-Stop Integrated Services (PTSP) in improving the quality of Motor Vehicle Tax payment services at SAMSAT Kabanjahe, Karo Regency. PTSP is positioned as an instrument of bureaucratic reform that aims to simplify procedures, increase service certainty, and strengthen the effectiveness of public services. The article uses a descriptive qualitative approach by collecting data through observation, in-depth interviews with SAMSAT officials and employees, as well as the taxpayer community, and documentation studies. The results of the discussion show that the implementation of PTSP is able to increase the certainty of service procedures and times, strengthen coordination between agencies, and encourage transparency and accountability of services. The support of standard operating procedures, the use of information technology, and the improvement of the competence of apparatus contribute to the creation of more effective and responsive services. Although some types of services still require a certain turnaround time, PTSP has increased public trust and satisfaction. This article emphasizes that strengthening PTSP has the potential to encourage taxpayer compliance and support the optimization of regional tax revenues in a sustainable manner.